Research on the structure of cargo flow in Latvia - Meirane, Elina (Transport, 2007)
The article provides analysis of the transport branch in Latvia in the period of time from 1999 to 2005. The notion of multimodality and its role in the development of logistics are viewed. By analyzing statistical data about the distribution of the cargo flow by each kind of transport, the author of the article has examined the existence of multimodality for creation of the logistics centers in Latvia. Furthermore, there is analysis of the cargo flow in the regions of Latvia and its distribution among the types of transport and kinds of communications in order to determine the territories prior to creation of a specific kind of a logistics center.First Published Online: 27 Oct 2010